2016
DOI: 10.1186/s13034-015-0088-x
|View full text |Cite
|
Sign up to set email alerts
|

Social support and gender differences in coping with depression among emerging adults: a mixed-methods study

Abstract: Background Depression affects a considerable proportion (12–25 %) of adolescents and so-called emerging adults (ages of 18 and 25). The aims of this study were to explore the relationship between perceived social support and depression in a sample of emerging adults, and subsequently to identify the type of social support young people consider most helpful in dealing with this type of emotional distress.MethodsA sample of 105 young persons (17–21 years of age) was selected from a previous longitudinal study to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 36 publications
(33 reference statements)
3
45
1
1
Order By: Relevance
“…For instance, in most western societies, the female part of the population tend to have lower socioeconomic status than the male, and a lower socioeconomic status has been associated with lower frequency of health care, regardless of actual psychiatric health [36]. Another example is coping strategies, the use of which may cause a person to reduce his or her need for care, and for which gender differences have been found when it comes to psychiatric health [37, 38]. Finally, if the disorder is displayed differently in women and men, such as is the case for e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in most western societies, the female part of the population tend to have lower socioeconomic status than the male, and a lower socioeconomic status has been associated with lower frequency of health care, regardless of actual psychiatric health [36]. Another example is coping strategies, the use of which may cause a person to reduce his or her need for care, and for which gender differences have been found when it comes to psychiatric health [37, 38]. Finally, if the disorder is displayed differently in women and men, such as is the case for e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work by Gregson et al [49] found that men were more likely than women to participate in events that involved alcohol use. Additionally, excessive alcohol use and self-reported depression may indicate social problems for which seeking social support (whether through sexual partnerships or otherwise) may be a coping mechanism [74,75]. Adjusting for these factors did not materially alter the degree to which gender modified the relationship between social capital and sexual concurrency in our study.…”
Section: Discussionmentioning
confidence: 54%
“…Studies have shown that in the context of LMICs, there is a need to identify and design interventions that are culturally relevant and sensitive to differences across caste and genders [ 64 , 65 ]. Differences among the participant’s caste, gender, age and educational status will help to guide the design of culturally salient interventions and inform future research across these domains of mental health.…”
Section: Discussionmentioning
confidence: 99%